Virtual tourism for cultural heritage: Transforming Generation Z’s engagement and visit intentions - Wajdi, Farid; Abas, Novel Idris; Setyawan, Anton Agus; Puspawati, Dewita (Turyzm/Tourism, 2025)
Applying the stimulus-organism-response (S-O-R) framework, this study’s main aim is to analyze the psychological mechanisms through which virtual reality (VR) experiences encourage Generation Z’s physical visit intentions to cultural heritage sites. Specifically, the research investigates how key VR features (stimulus: interactivity and telepresence) influence internal states (organism: place satisfaction, perceived authenticity and mental image), and how these states subsequently drive visit intentions (response). The study addresses a critical gap by focusing on these emotional and cognitive pathways. Data from 415 Indonesian Gen Z respondents who experienced Borobudur Temple via VR were analyzed using PLS-SEM. Results reveal that interactivity and telepresence significantly enhance place satisfaction, authenticity and mental imagery. Furthermore, perceived authenticity and a strong mental image are powerful predictors of visit intention, while place satisfaction shows no significant direct effect. These findings highlight the importance of emotional and cognitive factors in engaging Gen Z with cultural heritage tourism (CHT). The study offers valuable theoretical and practical insights, while the findings encourage cultural managers and policymakers to adopt VR technologies.